Cover image. (14th July 2019) - Xie, Nan; Yu, Pei; Liu, Haichao; Liu, Xiqiang; Hou, Jinsong; Chen, Xiaohua; Huang, Hongzhang; Wang, Cheng
Abstract : The cover image is based on the Original Article Validation of the International Tumor Budding Consensus Conference (2016) recommendations in oral tongue squamous cell carcinoma by Nan Xie et al., DOI10.1111/jop.12856 .